The Application Of E-Learning In Pai Learning At Mts Darul Ma’rifah Rangkasbitung: A Descriptive Study Of Its Advantages, Challenges, And Impacts - Agung Jaenudin; Wasehudin; Yuyun R. Uyuni; Fandy Adpen Lazzavietamsi; Rifyal Ahmad Lugow (LPPM STAI La Tansa Mashiro, 2026)
This study discusses the application of e-learning learning in Islamic Religious Education (PAI) subjects by highlighting its advantages, challenges, and impacts in the learning process. The method used in this study is qualitative descriptive with a literature analysis approach and empirical observation of the implementation of e-learning in the educational environment. The results show that e-learning in PAI learning has several advantages, such as flexibility of time and place, increased accessibility of learning resources, and a variety of more interactive learning media. However, there are challenges faced, such as limited technological infrastructure, digital gaps among students, and the need to improve teacher competence in managing digital-based learning. The impact of implementing e-learning in PAI includes increasing student learning motivation, the effectiveness of material delivery, and changes in interaction patterns between teachers and students. This study recommends strengthening technology infrastructure and training for educators to optimize the implementation of e-learning in PAI learning.